Implementation of transformative SEL standards for preparing future educators: A case study - Kristin Rush; Maiko Hata; Deirdre Hon; Lauren Vega O’Neil (Social and Emotional Learning: Research, Practice, and Policy)
Despite two decades of research on positive impacts of social and emotional learning (SEL), many teachers feel underprepared to support their students’ SEL. The purpose of this qualitative study is to describe the efforts of several of Oregon’s Educator Preparation Programs (EPPs) to conceptualize and carry out implementation of Oregon’s SEL standards to better support future teachers. We explored how EPPs across Oregon are addressing these new standards with interviews of four institutional representatives who are members of The Oregon Collaborative for SEL in Educator Preparation (OCSEP). The findings of this study provide valuable insights into the challenges and opportunities associated with implementing SEL state standards for EPPs and how to better support SEL standard implementation moving forward. The paper concludes with suggestions for future directions for SEL standards in educator preparation, emphasizing the need for ongoing evaluation, refinement, and adaptation to different teacher preparation contexts. Challenges and obstacles encountered during the implementation process are discussed.